Monetary regime and the co-ordination of wage setting - Steinar Holden (University of Oslo, Department of Economics, 2000)
International comparisons show that countries with co-ordinated wage setting generally have lower unemployment than countries with less co-ordinated wage setting. This paper argues that the monetary regime may affect whether co-ordination among many wage setters is feasible. A strict monetary regime, like a country-specific inflation target, to some extent disciplines wage setters, so that the consequences of uncoordinated wage setting are less detrimental than under a more passive monetary regime (eg a monetary union). Thus, the gains from co-ordination are larger under a passive regime. Under some circumstances a passive regime may induce co-operation in wage setting, and thus lower unemployment, when a stricter regime would not.
Keywords: E24; J5; E52; 330; Wage setting; co-ordination; equilibrium unemployment; monetary regime; monetary union; Geldpolitik; Inflation Targeting; Wirkungsanalyse; Lohnbildung; Vergleich; OECD-Staaten